Strategi keunggulan bersaing bank syariah berbasis digital: pendekatan analisis swot untuk inovasi layanan dan peningkatan pangsa pasar - Mustajab, Azwin Syahwadi (Maliki Interdisciplinary Journal, 2025)
Islamic banks are facing strong competition around the world. To stay competitive and grow, they need to use good strategic management. The banking industry is changing a lot, and there is a growing need for digital solutions. This research looks closely at the Strengths, Weaknesses, Opportunities, and Threats (SWOT) that Islamic banks face when trying to create new digital services. It also helps in making a strategy that uses digital tools to gain a competitive edge. Using SWOT analysis, the study finds that having the right strategy is key to improving competitiveness globally. This analysis helps Islamic banks use their strengths, like their good reputation based on Sharia principles and the variety of services they provide. It also helps them take advantage of external opportunities, such as the growth of the Islamic economy and support from regulators. At the same time, it helps Islamic banks deal with their weaknesses, like high costs and slow adoption of new technology. It also helps them prepare for threats from traditional banks and fintech companies. The best strategy should focus on making digital services more adaptable and competitive to improve customer satisfaction and increase their share of the market. Islamic banks are encouraged to invest more in financial technology, such as digital banking apps. They should also improve their system security and work closely with sharia-compliant fintech companies.